Funcionalidad familiar y su relación con exposición a violencia intrafamiliar en adolescentes del Bachillerato Zona 7 Ecuador 2016. - Procel González, Manuel José (2017)
It addresses a current problem that although family violence has always existed, it is of great interest to know how it influences the coexistence of the family and to apply preventive measures in the health of adolescents and environment, as family doctors. The present research establishes the relationship between family dysfunction and exposure to intrafamily violence through a cross - sectional analytic, with a random sample of 959 adolescents from Zone 7 of Ecuador, through the application of the CEV test, an internationally accepted survey For the analysis of exposure to violence, taking into account sociodemographic factors; In addition, the FFsil test was applied for family functionality. The results indicate that there is a direct relationship between exposure to intrafamily violence and family dysfunction, which is generated as a result of the family structure-mediated deterioration of family dynamics that may aggravate or mortify dysfunctionality, since at the same time , May be the cause or product of intrafamily violence. It was also found that from the perception of female adolescents, they are mostly exposed to violence within the family and that exposure to intrafamily violence and its correlate in family dysfunction is a cultural problem. Keywords: intrafamiliar; teenagers; Family dysfunction.